2019
DOI: 10.1155/2019/2154240
|View full text |Cite
|
Sign up to set email alerts
|

Total Delay in Treatment of Tuberculosis and Associated Factors among New Pulmonary TB Patients in Selected Health Facilities of Gedeo Zone, Southern Ethiopia, 2017/18

Abstract: Background. TB is an infectious disease caused by the bacillus Mycobacterium TB complex. It is a major public health concern causing devastating illness in millions of people each year and one of the top 10 causes of death worldwide following HIV pandemic. It demands huge costs each year for prevention, diagnosis, and treatment of TB. Global TB control progress depends on major advances in early diagnosis and treatment. Despite progress in providing diagnosis and preventive treatment of TB, big detection and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
7
19
4
3
Order By: Relevance
“…The median patient and health system delays in the current study were similar with previous findings reported in Ethiopia [ 9 , 17 ] and Africa [ 24 , 25 ]. However, the median patient delay was shorter than previous studies in Ethiopia [ 16 , 26 , 27 ] and longer than other reports from Ethiopia [ 28 , 29 ] and African [ 3 , 30 ] but the health system delay was shorter than studies in Ethiopia [ 13 , 14 ] which have similar median patient delay with this study. The reason for the shorter delay might be related to while two of the previous studies [ 16 , 29 ] were done in pastoralist communities; the current study was done in the agrarian community having relatively better accessibility and knowledge about TB compared to the pastoralist community.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The median patient and health system delays in the current study were similar with previous findings reported in Ethiopia [ 9 , 17 ] and Africa [ 24 , 25 ]. However, the median patient delay was shorter than previous studies in Ethiopia [ 16 , 26 , 27 ] and longer than other reports from Ethiopia [ 28 , 29 ] and African [ 3 , 30 ] but the health system delay was shorter than studies in Ethiopia [ 13 , 14 ] which have similar median patient delay with this study. The reason for the shorter delay might be related to while two of the previous studies [ 16 , 29 ] were done in pastoralist communities; the current study was done in the agrarian community having relatively better accessibility and knowledge about TB compared to the pastoralist community.…”
Section: Discussioncontrasting
confidence: 48%
“…Rural residents had higher odds of patient delay compared to the urban residents in health-seeking which was supported by studies done in Ethiopia [ 27 , 31 , 32 ], and Mediterranean region [ 7 ]. This might be related to the poor access of rural residents to health information and health facilities compared to the urban residents.…”
Section: Discussionmentioning
confidence: 57%
“…8 Many studies have been conducted both globally [9][10][11][12][13][14] and in the Indian context [15][16][17][18][19][20] to better understand TB patient care-seeking pathways. These studies find a number of factors to be commonly associated with delayed care-seeking, including lack of knowledge about TB, [10][11][12][13] being a woman, 11 14 20 lack of education, 11 living far from health facilities, 11 12 15 20 visiting informal care providers, 11 13 low income in Africa and Asia, 14 20 high income in South India, 16 age, 9 10 13 19 and tobacco and alcohol use. 16 21-25 Although existing research provides some insight into what drives people to seek care for their TB symptoms, these studies often only focus on a limited set of potential drivers, many of which are demographic variables.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…13 Based on a recent data, the TB incidence in Ethiopia is estimated at 80 -172/100,000 population, 1,14,15 .About 60,000 TB cases are not yet detected in the country, 15,16 and the national TB case notificateion rate and treatment success rate were reported to be 56% and 84%, respectively. 17,18 The low TB case notification rate may be linked to use of poor TB incidence estimation methods, 16,19 relying only on passive case detection approach to identify TB cases, 8,20,21 lack of adequate TB dignostic tools, 8,20,22 poor service availability and readiness, 8,21,23 high patient and facility delay, [24][25][26] and poor community awareness about TB . 14,18,27,28 The burdens of TB could be preventable under effective preventive strategies, early diagnosis and appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%